Animal assisted therapy and its mental health benefits (Research, Society and Development, 2022)
Animal Assisted Therapy is a therapeutic tool that aims to promote the patient's physical and emotional health and well-being. in this intervention it is used for different demands, whether physical or mental and is indicated for any stage of life. Thus, the study aimed to understand the benefits that animals bring to human health and how they help in the therapeutic process and well-being. This is an integrative review research. Data were selected through an electronic search in the following databases: VHL, Medline, PePSIC, SciELO and PsycINFO, in addition to some specific websites and journals on Assisted Therapy with Animals from 2010 to 2021. With the results, a sample was obtained of 11 studies, and it was found that AAT and living with animals promote well-being, emotions and positive behaviors, greater adherence to treatments, encourages the practice of activities, among others. It is concluded that it is important to analyze and develop new instruments to assist in practice, monitoring and forms of use.